B. R. Ay. YUDONEGORO : SOSOK PAKAR TARI KLASIK GAYA YOGYAKARTA - Sutiyati, Endang (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
<img src="data:image/png;base64,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